TEMPORAL TRENDS OF GESTATIONAL SYPHILIS IN BRAZIL, 2012-2022 - Pereira, Emile Danielly Amorim; Nogueira, Emanuelle Vieira; Frazão, Vanuza Silva (Seven Editora, 2026)
Gestational syphilis is an important public health problem due to the high risk of vertical transmission and the severe repercussions for the mother-child dyad. This is a descriptive epidemiological time-series study with a quantitative approach, using secondary data from the Notifiable Diseases Information System (SINAN) and the Live Birth Information System (SINASC). Detection rates per thousand live births were calculated, and trend Figures were produced. This study aimed to analyze the temporal trend of gestational syphilis in Brazil from 2012 to 2022. The results showed a continuous increase in reported cases of gestational syphilis, rising from 16,444 cases in 2012 to 78,872 in 2022, with a detection rate of 30.79 per thousand live births in the last year analyzed. Most infected pregnant women were aged 20–29 years, were of mixed race (brown), and had low educational attainment. The Southeast and Northeast regions accounted for the highest number of notifications, and the latent clinical form was the most prevalent. Gestational syphilis shows an upward trend in the country, associated with social inequalities and weaknesses in prenatal care. The need to strengthen surveillance actions, expand testing and treatment coverage, and enhance the role of nursing in the prevention and control of this condition is emphasized. DOI: https://doi.org/10.56238/sevened2026.008-081